Research on library collaboration through the Google Scholar database: A narrative literature review (2017–2023) - Sabilillah, Zahidah; Rizal, Edwin; Rukmana, Evi Nursanti (Faculty of Communication, Padjadjaran University, 2025)
Backgroud: Limited budgets have compelled libraries to innovate in order to ensure their sustainability. One effective strategy for addressing budget constraints is interlibrary collaboration. Interlibrary collaboration involves cooperative activities between two or more libraries and may also include partnerships with other information-related organizations, such as reference centers, data analysis institutions, and others. Such collaboration is essential because no single library, regardless of its scale or resources, can comprehensively collect all available information. Every library faces limitations in fully meeting users’ information needs. Interlibrary collaboration serves to bridge these gaps by enabling access to information that may not be available in a single institution. Purpose: This study aims to explore research on interlibrary collaboration by analyzing its historical development, supporting and inhibiting factors, and its impact on both users and institutions. Methods: The study employs a narrative literature review method, using the Google Scholar database to identify relevant references. A total of 14 journal articles were analyzed. Results: The findings suggest that interlibrary collaboration can be a viable solution for enhancing library collections. It also fosters stronger institutional relationships, as collaboration contributes to collection development and improves overall library quality. However, several challenges persist, such as limited personnel, which can slow down collaborative processes, and inadequate funding, which can hinder the sustainability of such initiatives. Despite these obstacles, interlibrary collaboration continues to evolve, offering opportunities to refine library strategies and improve the effectiveness of cooperative efforts.